Health burden attributable to ambient PM2.5 in China. (April 2017) - Song, Congbo; He, Jianjun; Wu, Lin; Jin, Taosheng; Chen, Xi; Li, Ruipeng; Ren, Peipei; Zhang, Li; Mao, Hongjun
Abstract: In China, over 1.3 billion people have high health risks associated with exposure to ambient fine particulate matter (PM2.5 ) that exceeds the World Health Organization (WHO) Air Quality Guidelines (AQG). The PM2.5 mass concentrations from 1382 national air quality monitoring stations in 367 cities, between January 2014 and December 2016, were analyzed to estimate the health burden attributable to ambient PM2.5 across China. The integrated exposure-response model was applied to estimate the relative risks of disease-specific mortality. Disease-specific mortality baselines in province-level administrative units were adjusted by the national mortality baseline to better reveal the spatial inequality of the health burden associated with PM2.5 . Our study suggested that PM2.5 in 2015 contributed as much as 40.3% to total stroke deaths, 33.1% to acute lower respiratory infection (ALRI, <5yr) deaths, 26.8% to ischemic heart disease (IHD) deaths, 23.9% to lung cancer (LC) deaths, 18.7% to chronic obstructive pulmonary disease (COPD) deaths, 30.2% to total deaths combining IHD, stroke, COPD, and LC, 15.5% to all cause deaths. The population weighted average (PWA) attributable mortality rates (10 −5 y −1 ) were 112.0 in current year analysis, and 124.3 in 10-year time lag analysis. The Mortality attributable to PM2.5 in 10-year time lag analysis (1.7 million) was 12% higher than the current year analysis (1.5 million). Our study also estimated site-specific annual PM2.5 concentrations in scenarios of achieving WHO interim targets (ITs) and AQG. The mortality benefits will be 24.0%, 44.8%, 70.8%, and 85.2% of the total current mortalities (1.5 million) when the PWA PM2.5 concentrations in China meets the WHO IT-1, IT-2, IT-3, and AQG, respectively. We expect air quality modeling and cost-benefits analysis of emission reduction scenarios and corresponding health benefits in meeting the site-specific annual PM2.5 concentrations (WHO IT-1, IT-2, IT-3, and AQG) this study raised. Graphical abstract: Highlights: Health burden attributable to PM2.5 were estimated with 3 years observed data. Province-level health benefits of meeting WHO interim standards in China were raised. 10-year time lag (1.7 million) and current mortality burden analysis (1.5 million) was conducted. Ambient PM2.5 pollution have been improved significantly from 2014 to 2016. Great spatial health inequality caused by PM2.5 should be considered.